The effect of authoritarian parenting style on online game addiction mediated by psychological well-being - Elvananta, Katamsi Tri Pratiwi Julia; Achmad, Rendy Alfiannoor; Shadiqi, Muhammad Abdan (Faculty of Psychology, Universitas Diponegoro, 2024)
Background: Online game addiction among Indonesian adolescents is a growing concern for parents. One contributing factor is the authoritarian parenting style. Purpose: This study examines the effect of authoritarian parenting on online game addiction, mediated by psychological well-being, based on the I-PACE theory. Method: Using a quantitative approach, 258 adolescents aged 16 to 20 years throughout Indonesia who actively playing online game were selected through purposive sampling (Mage = 18.74, SDage = 1.11). Data were collected via social media questionnaires. A sample size of 196 people was determined using Gpower. Data analysis employed Hayes’ mediation regression using PROCESS in IBM SPSS 25.Findings: Psychological well-being did not significantly mediate the effect of authoritarian parenting style on online game addiction behavior. Meanwhile, authoritarian parenting to online game addiction shows a positive relationship, β = 0.180, t(256) = 2.928, p < .05, 95% CIs [0.042, 0.215]. Authoritarian parenting style can also directly predict psychological well-being, β = -0.314, t(256) = -0.528, p < .05, 95% CIs [-0.484, -0.221]. In conclusion, authoritarian parenting directly predicts online game addiction without mediation by psychological well-being. Implication: Interventions targeting online game addiction should address parenting styles, focusing on parental education to reduce adolescents’ excessive gaming behavior.